Effect of Sulfuric Acid Immersion on the Carbon Characteristics of Cocoa Pod Husk - Octavia Marsha Pakpahan; Arya Widira Adi Nugraha; Susilowati; Caecilia Pujiastuti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Indonesia faces the challenge of dependency on fossil fuels, making the utilization of Biomass as a renewable energy source increasingly important. Cocoa pod husk, an abundant agricultural waste, has the potential to be converted into high-quality solid fuel through the torrefaction process. This study aims to analyze the effect of sulfuric acid (H?SO?) solution concentration and torrefaction temperature on the characteristics of carbon produced from cocoa pod husk, as well as to compare the results with the Indonesian National Standard (SNI) 8675-2018. The methods used include biomass preparation, soaking with various H?SO? concentrations (0, 0.4, 0.6, 0.8, and 1 M), and torrefaction at different temperatures (250, 275, 300, 325, and 350 °C). The product characteristics were analyzed using proximate analysis, calorific value testing, and SEM EDX. The results showed that increasing the acid concentration and torrefaction temperature significantly reduced the moisture, ash, and volatile matter content, while increasing the fixed carbon and calorific value. The optimum condition was obtained at 1 M H?SO?. soaking and 350 °C torrefaction, producing carbon with 0.17% moisture, 3.00% ash, 61.79% volatile matter, 35.04% fixed carbon, and a calorific value of 8071.34 cal/g. All parameters met the SNI 8675-2018 standard, indicating that acid-pretreated and torrefied cocoa pod husk has strong potential to be developed into high-quality solid fuel. Contribution to Sustainable  Development Goals (SDGs)SDG 7 (Affordable and Clean Energy) SDG 12 (Responsible Consumption and Production) SDG 13 (Climate Action)